Collaborative Strategic Reading in EFL Reading Classroom - Yentri Anggeraini; Novarita Novarita; Nurul Afifah (ETERNAL (English Teaching Journal), 2018)
This study aims to find out whether the collaborative strategic reading can significantly improve the students` reading comprehension achievement and what the students` perceptions on the use of collaborative strategic reading in EFL reading classroom are. The result showed that collaborative strategic reading can significantly improve the students reading achievement. The paired sample test showed the comparison of pretest and posttest score displayed the difference between scores. The mean difference was 15.000 and the value of t-obtained was 7.301. It was identified that sig. (2-tailed) or p value (0.00) was less than alpha value (0.05).  The students` dominant perceptions on the use of collaborative strategic reading were: students can summarize the text easily after using collaborative strategic reading and they can answer the questions of the narrative text after using story grammar strategy, collaborative strategic reading allows the students to think critically and can guide them in comprehending the text.